2019
DOI: 10.3389/fspor.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

Translating Science Into Practice: The Perspective of the Doha 2019 IAAF World Championships in the Heat

Abstract: Hot and humid ambient conditions may play a major role during the endurance events of the 2019 IAAF world championships, the 2020 summer Olympics and many other sports events. Here, various countermeasures with scientific evidence are put in perspective of their practical application. This manuscript is not a comprehensive review, but rather a set of applied recommendations built upon sound scientific reasoning and experience with elite athletes. The primary recommendation for an athlete who will be competing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
1
29
0
1
Order By: Relevance
“…The current results show a history of heat-related symptoms (57%) and some incidents of EHI (17%) in elite cyclists. This highlights the need for team doctors to be aware of the four ‘golden rules’ of heat stroke management (ie, early recognition, early diagnosis, rapid cooling, on-site cooling) 19. Our study showed that most elite cyclists use a pre-cooling strategy before competing in the heat, suggesting a need for race organisers to provide supporting facilities such as ice, cold-water bath, ice slurry machine, freezer for ice vest storage, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The current results show a history of heat-related symptoms (57%) and some incidents of EHI (17%) in elite cyclists. This highlights the need for team doctors to be aware of the four ‘golden rules’ of heat stroke management (ie, early recognition, early diagnosis, rapid cooling, on-site cooling) 19. Our study showed that most elite cyclists use a pre-cooling strategy before competing in the heat, suggesting a need for race organisers to provide supporting facilities such as ice, cold-water bath, ice slurry machine, freezer for ice vest storage, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The observation supports previous evidence that racewalking performance is highly correlated with submaximal exercise economy. 17 Heat acclimation/acclimatization training was implemented with the aim of reducing the performance decrement that can occur when nonacclimated athletes are competing in hot climates, 8,9,11 as part of a periodized program that included regular altitude training blocks. Simulated LHTL was implemented with the aim of increasing hypoxic dose and maintaining training intensity 3 to increase the potential for performance benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to departure for the Osaka World Championships, the athlete completed a 35-day LHTL block and 6-day post-LHTL recovery period. Concurrently, 1 heat acclimation session was completed per week, consistent with published recommendations for inducing heat adaptations in athletes, especially when combined with heat acclimatization performed immediately prior to major competitions, 1,9 and therefore, 6 sessions in total were implemented prior to the 14-day prerace heat acclimatization period (Kochi, Japan). Details of training sessions and environmental conditions are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the race day, the ambient temperature and relative humidity (RH) were 33 °C and 73%, respectively. This low completion rate may be attributed to environmental heat or related to exertional heat stroke [8]. Similar to the Doha race, substantial attention was paid to acclimation to the environment in Tokyo 2021 [9,10].…”
Section: Introductionmentioning
confidence: 99%